2000
DOI: 10.2174/0929867003374705
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and Anti-Cancer Activity of Polysaccharide-Protein Complexes

Abstract: In the last three decades, numerous polysaccharides and polysaccharide-protein complexes have been isolated from mushrooms and used as a source of therapeutic agents. The most promising biopharmacological activities of these biopolymers are their immunomodulation and anti-cancer effects. They are mainly present as glucans with different types of glycosidic linkages such as (1-->3), (1-->6)-beta-glucans and (1-->3)-alpha-glucans, and as true herteroglycans, while others mostly bind to protein residues as polysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
410
0
12

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(429 citation statements)
references
References 86 publications
(159 reference statements)
7
410
0
12
Order By: Relevance
“…2 and 3). The antitumor activity of β -glucans is known and has been reported in several studies with fungal (1 3),(1 6)-β -glucan, such as shizophylan, lentinam (Ooi and Liu 2000;Zhang et al 2005), (1 3),(1 6)-β -glucan from yeast (Kiho et al 1998). It can be explained that after implantation of tumor cells naturally elicited antitumor antibodies most probably occur, and they function similarly to exogenous antitumor mAbs by coating tumor cells with iC3b fragments (Hong et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…2 and 3). The antitumor activity of β -glucans is known and has been reported in several studies with fungal (1 3),(1 6)-β -glucan, such as shizophylan, lentinam (Ooi and Liu 2000;Zhang et al 2005), (1 3),(1 6)-β -glucan from yeast (Kiho et al 1998). It can be explained that after implantation of tumor cells naturally elicited antitumor antibodies most probably occur, and they function similarly to exogenous antitumor mAbs by coating tumor cells with iC3b fragments (Hong et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Especially, polysaccharides are considered to be one of the major active substances in mushrooms (Dalmo and Bøgwald, 2008). Polysaccharides isolated from mushrooms can have significant effects on the innate and adaptive immune response and therefore have the potential as immunostimulators with wide clinical and medicinal applications (Ooi and Liu, 2000;Tsan and Baochong, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several reports have found that ROS can stimulate the production of cytokines as a second messenger via the MAP kinase cascade in activated mast cells. 12,32) To determine the inhibitory effect of DBD glycoprotein on PMACIinduced ROS production, we measured the amounts of intracellular ROS using a fluorogenic tracer in PMACIstimulated HMC-1 cells. As described in ''Results,'' PMACI generated intracellular ROS in 30 min, but DBD glycoprotein suppressed PMACI-induced ROS production via inhibition of DCFH oxidation in the mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of these glycoproteins have attracted attention in the biochemical and medical areas because of their immunomodulatory and anti-oxidative activities. [12][13][14][15] In a previous study, we found that glycoprotein isolated from DBD (DBD glycoprotein) has an anti-apoptotic effect on radicalinduced cell death due to its strong radical scavenging activity, 16,17) but the role of DBD glycoprotein in mastcell biology is unclear.…”
mentioning
confidence: 99%